What role for deliberative minipublics in sustainability transformations? An emerging topic for sustainability science - Tim M. Daw; Simon West; Andrea Downing; Naghmeh Nasiritousi; Marina Lindell; Thomas Hahn; Mikael Karlsson; Tord Snäll; Daniel Lindvall (Sustainability Science, 2026)
Democracies struggle to translate sustainability science, and public concern into sufficiently transformative actions. Ongoing polarization, politicization and disinformation extenuate this challenge. Some scholars suggest that deliberative democratic innovations can help to bridge science, public understanding and will formation, and policy implementation in the face of vested interests. In light of these challenges, we introduce deliberative mini-publics (DMPs), and why they are of interest to sustainability scientists. DMPs are distinguished from participatory methods more familiar to sustainability scientists by their random and stratified selection of ‘ordinary citizens’. An emphasis is also placed on facilitated deliberation, access to information and learning. Evidence shows that the particular conditions of DMPs can support more deliberative and informed reasoning and offer a considered public voice for decision-makers, fellow citizens and sustainability scientists. However, evidence of their wider effect on society and sustainability is mixed and warrants further examination. We draw on examples from emerging research and experience of DMPs to conceptualize three broad mechanisms for how they could potentially enhance the relationship between sustainability science, publics and politics. These differ based on whether they are primarily aiming to (1) inform policy-makers, (2) support public discourse, or (3) enhance transdisciplinary science. We also explore whether DMPs can challenge unsustainable systems and contribute to transformation through visioning, strategizing transitions, and scrutinizing the decisions of public agencies. We encourage experimentation and critical research on DMPs for sustainability transformations to test and better understand their potential.

A meaningful performative experience: using Forum Theatre as an ethical method in sustainability science - María Mancilla García; Lena Bertemes Lalia; Marlino Mubai; Tilman Hertz; Elizabeth Maria Drury O’Neill; Caroline Abunge; Salomão Olinda Bandeira; François Bousquet; Christopher Cheupe; Dadivo José Combane; Tim Daw; Nyawira Muthiga; et al. (Sustainability Science, 2025)
Sustainability scientists have engaged in extensive discussions on ethical ways of doing research and argued on the importance of co-production approaches to counter knowledge extractivism. The specific issue of research fatigue, often associated with knowledge extractivism, and the possible methods to counter it, have however received less attention. This paper seeks to contribute to discussions on ethical ways of doing research by focusing on our experience of using theatre, specifically, Forum Theatre, to investigate divergent perceptions of environmental change and related tensions among selected coastal communities in Kenya and Mozambique. We argue that Forum Theatre constitutes an ethical method for sustainability scientists for four reasons: (i) it allows to co-produce knowledge with participants; (ii) it facilitates horizontal exchange; (iii) it creates joyful moments; and (iv) it enables the transmission of skills that remain with participants beyond project durations. The paper engages with these four themes, first theoretically and then proposing a reflection based on our project experience. In the last section, we warn against some of the limitations of the approach.

What do you mean 'Climate Change'? An analysis of climate change framings in three climate assemblies - Corinna Zeitfogel; Tim Daw; David Collste (Environmental Science & Policy, 2024)

Life satisfaction in coastal Kenya and Mozambique reflects culture, gendered relationships and security of basic needs: Implications for ecosystem services - Tim M. Daw; Nicole J. Reid; Sarah Coulthard; Tomas Chaigneau; Vilma Machava António; Christopher Cheupe; Geoff Wells; Edgar Bueno (Ecosystem Services, 2023)

Economic incentives drive the conversion of agriculture to aquaculture in the Indian Sundarbans: Livelihood and environmental implications of different aquaculture types - Sandip Giri; Tim M. Daw; Sugata Hazra; Max Troell; Sourav Samanta; Oindrila Basu; Charlotte L. J. Marcinko; Abhra Chanda (Ambio, 2022)

Navigating Complexities: Agent-Based Modeling to Support Research, Governance, and Management in Small-Scale Fisheries - Emilie Lindkvist; Nanda Wijermans; Tim M. Daw; Blanca Gonzalez-Mon; Alfredo Giron-Nava; Andrew F. Johnson; Ingrid van Putten; Xavier Basurto; Maja Schlüter (Frontiers in Marine Science, 2020)

On the other end of research: exploring community-level knowledge exchanges in small-scale fisheries in Zanzibar - Viola Hakkarainen; Tim M. Daw; Maria Tengö (Sustainability Science, 2020)
Sustainability science has increasingly adopted more action-oriented approaches in an attempt to mobilise and implement a broad knowledge base to sustain human wellbeing and promote sustainable development. There is an increasing recognition of the importance of knowledge exchange (KE) between scientists and end users of research for enhancing social, environmental and economic impacts of research. Here, we explore the process of KE through close observation of two cases of KE between external PhD researchers and local actors in small-scale fisheries at the community level in Zanzibar, Tanzania. First, we address context by examining perceptions of research held by actors at community level and patterns of interactions and flows of benefits between external researchers and local actors including fisheries managers, local research institute as well as fishers and traders. Second, we unpack experiences of actors engaged in the cases of KE. The study draws attention to KE processes in the Global South and actors outside decision-making processes in fisheries management. The study concludes that as KE is a complex and dynamic process and that (i) history and relationships between actors shape the outcomes of KE, (ii) KE includes more than knowledge-based processes and outcomes because multiple incentives of different actors shape KE and how it is experiences and (iii) knowledge-based outcomes of KE are complex and unpredictable as different actors create their own meaning from shared information. The results exemplify the inevitably complex and unpredictable nature of KE processes and their outcomes, and provide insight into how KE can contribute to science–society relationships.

An Experimental Approach to Exploring Market Responses in Small-Scale Fishing Communities - Elizabeth Drury O’Neill; Therese Lindahl; Tim Daw; Beatrice Crona; Alice Joan G. Ferrer; Robert Pomeroy (Frontiers in Marine Science, 2019)

Incorporating basic needs to reconcile poverty and ecosystem services - Tomas Chaigneau; Sarah Coulthard; Katrina Brown; Tim M. Daw; Björn Schulte‐Herbrüggen (Conservation Biology, 2019)
Conservation managers frequently face the challenge of protecting and sustaining biodiversity without producing detrimental outcomes for (often poor) human populations that depend on ecosystem services for their well‐being. However, mutually beneficial solutions are often elusive and can mask trade‐offs and negative outcomes for people. To deal with such trade‐offs, ecological and social thresholds need to be identified to determine the acceptable solution space for conservation. Although human well‐being as a concept has recently gained prominence, conservationists still lack tools to evaluate how their actions affect it in a given context. We applied the theory of human needs to conservation by building on an extensive historical application of need approaches in international development. In an innovative participatory method that included focus groups and household surveys, we evaluated how human needs are met based on locally relevant thresholds. We then established connections between human needs and ecosystem services through key‐informant focus groups. We applied our method in coastal East Africa to identify households that would not be able to meet their basic needs and to uncover the role of ecosystem services in meeting these. This enabled us to identify how benefits derived from the environment were contributing to meeting basic needs and to consider potential repercussions that could arise through changes to ecosystem service provision. We suggest our approach can help conservationists and planners balance poverty alleviation and biodiversity protection and ensure conservation measures do not, at the very least, cause serious harm to individuals. We further argue it can be used as a basis for monitoring the impacts of conservation on multidimensional poverty.

Masked, diluted and drowned out: how global seafood trade weakens signals from marine ecosystems - Beatrice I Crona; Tim M Daw; Wilf Swartz; Albert V Norström; Magnus Nyström; Matilda Thyresson; Carl Folke; Jonas Hentati‐Sundberg; Henrik Österblom; Lisa Deutsch; Max Troell (Fish and Fisheries, 2016)
Nearly 40% of seafood is traded internationally and an even bigger proportion is affected by international trade, yet scholarship on marine fisheries has focused on global trends in stocks and catches, or on dynamics of individual fisheries, with limited attention to the link between individual fisheries, global trade and distant consumers. This paper examines the usefulness of fish price as a feedback signal to consumers about the state of fisheries and marine ecosystems. We suggest that the current nature of fisheries systems and global markets prevent transmission of such price signals from source fisheries to consumers. We propose several mechanisms that combine to weaken price signals, and present one example – the N orth S ea cod – to show how these mechanisms can be tested. The lack of a reliable price feedback to consumers represents a challenge for sustainable fisheries governance. We therefore propose three complimentary approaches to address the missing feedback: (i) strengthening information flow through improved traceability and visibility of individual fishers to consumers, (ii) capitalizing on the changing seafood trade structures and (iii) bypassing and complementing market mechanisms by directly targeting citizens and political actors regarding marine environmental issues through publicity and information campaigns. These strategies each have limitations and thus need to be pursued together to address the challenge of sustainability in global marine fisheries.

Women Fish Traders on the Kenyan Coast: Livelihoods, Bargaining Power, and Participation in Management - Naomi Matsue; Tim Daw; Lucy Garrett (Coastal Management, 2014)

Connecting Marine Ecosystem Services to Human Well-being: Insights from Participatory Well-being Assessment in Kenya - Caroline Abunge; Sarah Coulthard; Tim M. Daw (Ambio, 2013)

Design Factors and Socioeconomic Variables Associated with Ecological Responses to Fishery Closures in the Western Indian Ocean - Tim M. Daw; Joshua E. Cinner; Timothy R. McClanahan; Nicholas A. J. Graham; Shaun K. Wilson (Coastal Management, 2011)

Lag Effects in the Impacts of Mass Coral Bleaching on Coral Reef Fish, Fisheries, and Ecosystems - NICHOLAS A. J. GRAHAM; SHAUN K. WILSON; SIMON JENNINGS; NICHOLAS V. C. POLUNIN; JAN ROBINSON; JUDE P. BIJOUX; TIM M. DAW (Conservation Biology, 2007)
Recent episodes of coral bleaching have led to wide‐scale loss of reef corals and raised concerns over the effectiveness of existing conservation and management efforts. The 1998 bleaching event was most severe in the western Indian Ocean, where coral declined by up to 90% in some locations. Using fisheries‐independent data, we assessed the long‐term impacts of this event on fishery target species in the Seychelles, the overall size structure of the fish assemblage, and the effectiveness of two marine protected areas (MPAs) in protecting fish communities. The biomass of fished species above the size retained in fish traps changed little between 1994 and 2005, indicating no current effect on fishery yields. Biomass remained higher in MPAs, indicating they were effective in protecting fish stocks. Nevertheless, the size structure of the fish communities, as described with size‐spectra analysis, changed in both fished areas and MPAs, with a decline in smaller fish ( 45 cm). We believe this represents a time‐lag response to a reduction in reef structural complexity brought about because fishes are being lost through natural mortality and fishing, and are not being replaced by juveniles. This effect is expected to be greater in terms of fisheries productivity and, because congruent patterns are observed for herbivores, suggests that MPAs do not offer coral reefs long‐term resilience to bleaching events. Corallivores and planktivores declined strikingly in abundance, particularly in MPAs, and this decline was associated with a similar pattern of decline in their preferred corals. We suggest that climate‐mediated disturbances, such as coral bleaching, be at the fore of conservation planning for coral reefs.